(untitled) (The South East European Journal of Economics and Business, 2023)
This paper studies the extent individuals are willing to undertake energy efficiency measures, with evidence coming from a developing country (Bosnia and Herzegovina). The goal of this paper is to analyze energy savings behaviors, aiming to understand what is typically meant under the term energy efficiency, who is more likely to know the meaning, and the extent individuals are willing to undertake some energy efficiency measures. The sample size used in this paper is a random stratified sample of 1,415 individuals coming from various backgrounds. Our logistic regression models found no statistically significant predictor across all ten measures used in the study. However, past experience, age, and being married are relatively common across these ten energy-saving behaviors. These results might be beneficial in defining policies in order to promote energy-saving behaviors.